If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 + -19 = 3(x + -4) Combine like terms: 40 + -19 = 21 21 = 3(x + -4) Reorder the terms: 21 = 3(-4 + x) 21 = (-4 * 3 + x * 3) 21 = (-12 + 3x) Solving 21 = -12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 21 + -3x = -12 + 3x + -3x Combine like terms: 3x + -3x = 0 21 + -3x = -12 + 0 21 + -3x = -12 Add '-21' to each side of the equation. 21 + -21 + -3x = -12 + -21 Combine like terms: 21 + -21 = 0 0 + -3x = -12 + -21 -3x = -12 + -21 Combine like terms: -12 + -21 = -33 -3x = -33 Divide each side by '-3'. x = 11 Simplifying x = 11
| 8-72y=95-15y | | 7x^2+2x-15=0 | | Y(1-x)DX+x(1+y)dy=0 | | 2t+4u=40 | | 27-17=5(x-8) | | 20x-16=18x+6 | | -(13+g)=-9 | | 61+4y-28=15y-9-4y | | 80=91x | | 2.9y+1.7=3.5+23y | | -2(-3x-1)-3=-4 | | 9y-9=7y+1 | | x+18+4x=-48-4x-51 | | 4(7x+5)-48x=10x-10 | | 9p+8q=108 | | 6x-12=4(x+7) | | 2cos^2(x)-4cos(x)=0 | | (9x^2-7)*(9x^2+7)= | | 2/9-3 | | 8P+4Q=68 | | x^2+ln(-x+4)= | | 2(x+5)=8is | | 25s^2-81=0 | | 13=5-13+3c | | 2x+-5y+9=0 | | 13=5+4a | | 7428=p*6 | | 13-5=4a | | f(x)=-120+5x | | g+g+g=(1+g) | | 1-12=z/-4 | | -15x+25=220 |